" Hybrid wars and their impact on the future of global conflict" - Assistant Professor Dr.Saddam Marir Hamad (Tikrit Journal For Political Science, 2024)
War is a modern, modern and developed phenomenon throughout the history of mankind. Its impact was no more than that surrounding man himself. However, with the creation of an industrial industry that has a strong impact on weapons and expands their range, as well as advanced industry and the way of life in general, together created calls for war and self-defense or confronted with... His enemies, the concepts of war have witnessed radical transformations and changes in recent years, which prompted the countries of the world to rebuild their future perception of their national security, and all of this begins because of the technological, technical and scientific progress that began on the global scene, and since then accelerated progress and development begins new types. . From wars (such as hybrid wars, cyber war, virus (biological) war, information war, water war, wars of internal chaos, and many other wars), as the methods and tools of war, their intensity, and the extent of their impact changed with them, which prompted countries to make great efforts in order to develop their capabilities and means of defense and the continuous search for development Tools of attack, as well as protecting their countries from any threat they face, especially since the international system is no longer limited to countries only. Rather, there are international and non-international actors who may be people who threaten the security and safety of major countries. The world has recently faced a fierce war and a real danger that threatened global security and was stopped. The Earth was unable to operate for many months, which was caused by the outbreak of a biological hazard with the emergence of (Covid-19) In the Chinese city of Wuhan, which was classified as a global pandemic, despite the lack of evidence for this, the presence of laboratories for real deadly viruses proves the existence or occurrence of biological wars between countries, so the types of these wars must be identified and classified appropriately and an attempt is made to protect human societies from such wars. And maintain global security and peace.